Studies on the Sensory and Microbiological Quality of Pizzas Sold in and around Greater Hyderabad Municipal Corporation - Reddy, D. Venkat; Yogesh, M.; G. Sri Mahitha; Reddy, K. Lahari; Krishnaiah, N. (International Journal of Livestock Research, 2019)
A study was conducted to assess the organoleptic and microbiological quality of pizzas sold in various outlets in and around Greater Hyderabad Municipal Corporation Telangana State, India. The sensory scores were higher for reputed brands, least for street vendors and in between for moderate fast food shops. The total viable count was highest (8.8 106CFU/gm) in burgers from street vendors, lowest (3.0 105CFU/gm) from reputed brands, whereas it is intermediate (3.56 6CFU/gm) from moderate fast food centers. The coliforms count and faecal coliform in A study was conducted to assess the organoleptic and microbiological quality of pizzas sold in various outlets in and around Greater Hyderabad Municipal Corporation Telangana State, India. The sensory scores were higher for reputed brands, least for street vendors and in between for moderate fast food shops. The total viable count was highest (8.8 106CFU/gm) in burgers from street vendors, lowest (3.0 105CFU/gm) from reputed brands, whereas it is intermediate (3.56 6CFU/gm) from moderate fast food centers. The coliforms count and faecal coliform in the burgers collected from reputed brands, moderate fast food centers and street vendors was4.0 103 and 1.2 ,4.2 104 and 2.1 104and 4.8 104 and 9.8 103CFU/gm respectively. The yeast and moulds counts were 1.9 104, 2.6 5and 2.0 106CFU/gm in samples from reputed brands, moderate fast food centres and street vendors respectively. The incidence and counts of Staphylococcus spp., E. coli, Salmonella spp., Vibrio spp. and Listeria spp. were also noted. the burgers collected from reputed brands, moderate fast food centers and street vendors was4.0 103 and 1.2 ,4.2 104 and 2.1 104and 4.8 104 and 9.8 103CFU/gm respectively. The yeast and moulds counts were 1.9 104, 2.6 5and 2.0 106CFU/gm in samples from reputed brands, moderate fast food centres and street vendors respectively. The incidence and counts of Staphylococcus spp., E. coli, Salmonella spp., Vibrio spp. and Listeria spp. were also noted.